2015
DOI: 10.1177/0301006615614489
|View full text |Cite
|
Sign up to set email alerts
|

Haptic Object Recognition is View-Independent in Early Blind but not Sighted People

Abstract: Object recognition, whether visual or haptic, is impaired in sighted people when objects are rotated between learning and test, relative to an unrotated condition, i.e., recognition is view-dependent. Loss of vision early in life results in greater reliance on haptic perception for object identification compared to the sighted. Therefore, we hypothesized that early blind people may be more adept at recognizing objects despite spatial transformations. To test this hypothesis, we compared early blind and sighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…They stated that the tactus is a crucial sense, which can be used to substitute for vision. Results of the experiments conducted by Occelli et al [58] show that people with early-onset blindness reflect greater haptic sensitivity than the sighted. They also validated the hypothesis that people losing vision early can recognize objects by their haptic perception regardless of spatial transformations.…”
Section: Tactusmentioning
confidence: 94%
“…They stated that the tactus is a crucial sense, which can be used to substitute for vision. Results of the experiments conducted by Occelli et al [58] show that people with early-onset blindness reflect greater haptic sensitivity than the sighted. They also validated the hypothesis that people losing vision early can recognize objects by their haptic perception regardless of spatial transformations.…”
Section: Tactusmentioning
confidence: 94%
“…So far, the available evidence with blind adults has yielded conflicting results. On one side, several studies documented that blind people, when directly asked, can learn and are able to correctly use various geometric concepts such as symmetry or mental rotations (Bauer et al, 2015;Carpenter & Eisenberg, 1978;Cattaneo et al, 2014Cattaneo et al, , 2010Marmor & Zaback, 1976;Occelli, Lacey, & Sathian, 2016). These results show that blind adults can successfully acquire geometric foundations via touch, but whether they use the same geometric intuitions as sighted individuals to drive haptic spatial grouping and similarity judgments remain an open question.…”
Section: Fig 1 Methodsmentioning
confidence: 99%
“…However, several previous studies showed that blind participants do possess and can successfully master the geometric concepts which they failed to spontaneously detect in the current work. For instance, blind participants succeeded in perceiving symmetry relations when directly comparing symmetrical and non-symmetrical figures (Bauer et al, 2015;Cattaneo et al, 2014Cattaneo et al, , 2010 and in performing mental rotations under more focused experimental conditions (Carpenter & Eisenberg, 1978;Marmor & Zaback, 1976;Occelli et al, 2016). Some of these studies even showed that the neural representations of certain features such as symmetry are shared between the blind and sighted populations (Bauer et al, 2015).…”
Section: Differences Between Visual and Tactile Geometrical Explorationmentioning
confidence: 99%
“…This performance degradation is visible in the sighted regardless of the sense involved in recognition, that is vision or touch ( Lacey et al, 2007 ). On the contrary, Occelli et al (2016) showed that in the congenitally blind object recognition is view-independent, that is accuracy is not affected by the rotation of the learned object. Another result of this study is that overall no difference in performance between blind and sighted was observed.…”
Section: Introductionmentioning
confidence: 98%